Issues impeding quality inspection of a solar farm construction / Hafizah Mohd Latif, Noor Sahidah Samsudin and Faris Anwar Hussin - Mohd Latif, Hafizah; Samsudin, Noor Sahidah; Hussin, Faris Anwar (Universiti Teknologi MARA, Perak, 2021)
The quality inspection of a solar farm construction is essential in ensuring that the structural base to receive photovoltaic modules is built as planned. The aim of this exploratory paper is to discover issues that could impede an effective quality inspection. The evidence suggests that unethical behaviour of the site personnel is the major factor, apart from poor drainage system and poor documentation management, which have impeded the delivery of quality. Unethical behaviour and the racism issues, which were unexpected would be fruitful areas for further studies. The potential solar investor and related stakeholders shall consider the above issues in future for a more sustainable lifecycle.